Overcoming Undergraduate Nursing Education Challenges During the Pandemic - Melissa Abreu; Carolina Ferreiro; Danielle Garcia; Gisell Gonzalvo; Erika Nusbaum; Beatrice Sikah (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2021)
Despite the challenges encountered throughout the COVID-19 pandemic, undergraduate nursing education was able to pivot and prevent cessation as faculty and students utilized various virtual platforms to provide didactic, skills lab, and clinical exposure without delaying graduation for many students. Although nothing could replace the hands-on human interaction a clinical rotation provided, virtual experiences aligned with the course content helped students reinforce the concepts taught in the corresponding didactic portion proving this to be beneficial in its own way. As faculty, we rose to the challenge in fostering a supportive environment to keep students motivated to learn and engaged in coursework.